MANAJEMEN KEUANGAN MADRASAH - Muhammad Roihan Daulay (Universitas Muhammadiyah Tapanuli Selatan, 2017)
The title of this paper is financial management of Madrasah. To form the high quality of Islamic education so it would be need to have the effective, accountable, and transparent financial management. The importance of this would mention such as planning, operating, implementation, evaluation of the madrasah financial, including of madrasah ibtidaiyah, tsanawiyah and aliyah becomes an important point to recognize. By the realization of financial management based on the above principle, it is hoped the madrasah would be better. However, if the financial management were not suitable to those principles, as the result it will be fail to educated the youth generation